Advances in diagnosis, classification, pathophysiology, and management of trigeminal neuralgia. Issue 9 (September 2020) - Bendtsen, Lars; Zakrzewska, Joanna Maria; Heinskou, Tone Bruvik; Hodaie, Mojgan; Leal, Paulo Roberto Lacerda; Nurmikko, Turo; Obermann, Mark; Cruccu, Giorgio; Maarbjerg, Stine
Summary: Trigeminal neuralgia is a very painful neurological condition with severe, stimulus-evoked, short-lasting stabbing pain attacks in the face. The past decade has offered new insights into trigeminal neuralgia symptomatology, pathophysiology, and treatment, leading to a change in the classification of the condition. An accurate diagnosis is crucial because neuroimaging interpretation and clinical management differ among the various forms of facial pain. MRI using specific sequences should be a part of the diagnostic workup to detect a possible neurovascular contact and exclude secondary causes. Demonstration of a neurovascular contact should not be used to confirm a diagnosis but rather to facilitate surgical decision making. Carbamazepine and oxcarbazepine are drugs of first choice for long-term treatment, whereas microvascular decompression is the first-line surgery in medically refractory patients. Advances in neuroimaging techniques and animal models will provide further insight into the causes of trigeminal neuralgia and its pathophysiology. Development of more efficacious treatment options is highly warranted.